Information Technology Governance Audit In The Financial Sector Using Cobit 5 Framework - Tuti Dharmawati; Pandu Adi Cakranegara; Sitti Arni; Miftahorrozi Miftahorrozi; Ahmad Jurnaidi Wahidin (Institute of Computer Science (IOCS), 2022)
Companies require information technology to assist their operational tasks, such as in the banking sector. PT. Penkalis Sridanta As a provider of labor, money is one of the most crucial aspects of the business. Existing Information Technology in the financial sector is unable to maximize the company's performance, particularly in the handling of financial data, due to current issues. To maintain optimal Information Technology management, it is necessary to measure the current level of Information Technology governance and compare it to the level required by the organization, particularly in the financial industry. This assessment relates to the APO (Align, Plan, and Organize) domain of COBIT 5, with a particular emphasis on the APO01 (Manage the Information Technology Management Framework), APO02 (Manage Strategy), and APO06 (Manage Budget and Costs) sub-domains. Service Contracts), APO12 (Manage Risk). The conducted maturity level assessment reveals that the organization, particularly in the financial sector, is still at level 3 (Defined), with level 4 as the aim (Managed).